Species identification, antifungal susceptibility, and clinical feature association of Aspergillus section Nigri isolates from the lower respiratory tract. (26th June 2019) - Takeda, Keita; Suzuki, Junko; Watanabe, Akira; Matsuki, Mei; Higa, Katsuyuki; Inoue, Eri; Akashi, Shunsuke; Shimada, Masahiro; Kawashima, Masahiro; Ohshima, Nobuharu; Fukami, Takeshi; Masuda, Kimihiko; et al.
Abstract: Species of Aspergillus section Nigri are generally identified by molecular genetics approaches, whereas in clinical practice, they are classified as A. niger by their morphological characteristics. This study aimed to investigate whether the species of Aspergillus section Nigri isolated from the respiratory tract vary depending on clinical diagnosis. Forty-four Aspergillus section Nigri isolates isolated from the lower respiratory tracts of 43 patients were collected from February 2012 to January 2017 at the National Hospital Organization (NHO) Tokyo National Hospital. Species identification was carried out based on β-tubulin gene analysis. Drug susceptibility tests were performed according to the Clinical and Laboratory Standards Institute (CLSI) M38 3rd edition, and the clinical characteristics were retrospectively reviewed. A. welwitschiae was isolated most frequently, followed by A. tubingensis . More than half of the A. tubingensis isolates exhibited low susceptibility to azoles in contrast to only one A. welwitschiae isolate. Approximately three quarters of the patients from whom A. welwitschiae was isolated were diagnosed with colonization, whereas more than half the patients from whom A. tubingensis was isolated were diagnosed with chronic pulmonary aspergillosis (CPA). More attention needs to be given to the drug choice for patients with CPA with Aspergillus section Nigri infection because A. tubingensis, which was found to be frequently azole-resistant, was the most prevalent in these patients.